Word Of Mouth dan Cita Rasa: Sebuah Pendekatan Planned Behavior pada Keputusan Pembelian - Yunita Lestari; Dina Lusianti; Etni Marliana (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to analyze the effect of word of mouth and taste on buying interest and purchase decisions at bakery in Kudus. The theory used in this research is the theory of planned behavior. The method used in this research is quantitative, with explanatory research as the type of research. Sampling is the research used a purposive sampling technique consisting of 125 respondents. The data analysis used is SEM which is operated through the AMOS program. The results of this study indicate that word of mouth has a positive and insignificant effect on buying interest and purchase decisions, taste has a positive and significant effect on buying interest and purchase decisions, and buying interest has a positive and significant on purchase decisions, as well as buying interest can’t be an intervening variable on the influence of word of mouth and taste on purchase decisions.